Trouble in the Making? : The Future of Manufacturing-Led Development - Hallward-Driemeier, Mary (Washington, DC: World Bank, 2017)
Globalization and new technologies are impacting the desirability and feasibility of what has historically been the most successful development strategy. Manufacturing has been seen as special, promising both productivity gains and job creation. But trade is slowing. Global value chains (GVC) are maturing. Robotics, artificial intelligence, 3D printing, and the Internet of things are shifting what makes locations attractive for production and threatening significant disruptions in employment. There is a risk of increased polarization, within countries and across countries.